Assessing Healthcare Students’ Self-Efficacy in Disaster Response: A Cross-Sectional Analysis - Şenol, Aydın; Adıyaman, Abdülkerim; Okuyan, Canan Birimoglu (Makara Journal of Health Research, 2025)
Background: Assessing healthcare students’ self-efficacy in disaster response is crucial for preparing them to effectively manage real-world disaster situations. This study aimed to assess the self-efficacy status of healthcare students in disaster response. Methods: The data for this cross-sectional analysis were gathered from 498 healthcare students between November 18, 2023, and February 14, 2024, using an individual diagnostic form and the disaster-response self-efficacy (DRSE) scale. This scale is used to assess an individual’s self-efficacy in responding effectively to disasters, including on-site rescue competency, disaster psychological nursing competency, disaster role quality, and adaptation competency. Results: The mean age of the students enrolled in the study was 21.7 ± 3.56 years. A statistically significant difference was observed between the total DRSE scale score and the subdimension scores of students who were male, in the fourth grade, studying in the nursing department, exposed to a disaster, and enrolled in a course or training on disaster management (p < 0.05). Conclusions: The results emphasize the importance of education, training, and prior experience in enhancing DRSE among healthcare students. Tailored interventions and comprehensive instructional activities are thus essential to improve preparedness and to ensure that students can effectively handle disaster scenarios.